Islam and Pancasila Democratic Economics: Islamic Criticism of Capitalist and Socialist Economic Thought - Zulkarnaen Zulkarnaen; Maisaroh Maisaroh; Iiz Izmuddin (Universitas 17 Agustus 1945 Semarang, 2024)
This research was conducted with the aim of providing information about Islam and Pancasila Democratic Economics with Islamic criticism of Capitalist and socialist Economics. The research method uses literature study, by explaining theories related to titles obtained from books, journals and online media. This research found that when juxtaposed Islamic economics and Pancasila economics have the same concept and aim at human welfare and justice. The capitalist and socialist economic systems have been criticized by Islamic economics because of injustice, exploitation and imbalance. By integrating Islamic economic principles, Indonesia can develop a more just, stable and sustainable economic system in accordance with the values ​​of Pancasila and Islamic teachings.